MEDICINAL PLANTS AND BIOLOGICALLY ACTIVE SUBSTANCES WITH ANTIFUNGAL PROPERTIES - ANDREY A. Mar‘In; NATALIA E. Kolomiets (Фундаментальная и клиническая медицина)
Fungal diseases, caused by pathogenic fungi from air, soil, water, plants, and even the human body, are dangerous for humans of all age groups. Currently, commercially available antifungal agents mainly include synthetic products having numerous contraindications and severe side effects. Another problem is a widespread resistance of fungi to antifungal agents. Therefore, the search of medicinal plants containing antifungal substances for the development of non-toxic plant drugs is rapidly ongoing. Experimental studies show the high efficiency of even minimum concentrations of biologically active substances (essential oils, saponins, flavonoids etc.) against the most common fungal pathogens (Microsporum canis, Trichophyton rubrum, Trichophyton mentagrophytes). These data indicate the possibility of using medicinal plants to prepare novel efficient antifungal agents.